The Impact of Community-Based Tuberculosis Education on Public Attitudes in Jambi City, Indonesia - Keisya Dzikrina Putri; Erny Kusdiyah; Esa Indah Ayudia (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis (TB) remains one of the most persistent infectious diseases worldwide, particularly in Indonesia, which ranks second globally in the number of TB cases. This study aimed to determine the effect of community-based TB education conducted by the Penabulu STPI community on the attitudes of Jambi City residents. The research used a quantitative approach with a pre-test and post-test design. Data were collected using questionnaires to measure participants’ attitudes before and after the intervention. Data were analyzed using univariate and bivariate analyses, with the Wilcoxon signed rank test applied to determine significant differences in pre-test and post-test results. The findings revealed that most respondents were adults (85%), predominantly female (89%), and had completed senior high school (54%). Attitudes improved significantly, shifting from 19.2% negative responses before the intervention to 100% positive responses after. The Wilcoxon signed-rank test showed a statistically significant difference between respondents’ attitude scores before and after the intervention (Z = –8.395, p < 0.001).These results demonstrate that community-based education effectively enhances public awareness and encourages positive attitudes toward TB prevention and treatment, highlighting the essential role of grassroots initiatives in controlling the spread of tuberculosis.